Pregnancy outcomes of women conceiving on antiretroviral therapy (ART) compared to those commenced on ART during pregnancy. - Theron, Gerhard; Brummel, Sean; Fairlie, Lee; Pinilla, Mauricio; McCarthy, Katie; Owor, Maxensia; Chinula, Lameck; Makanani, Bonus; Violari, Avy; Moodley, Dhayendre; Chakhtoura, Nahida; Browning, Renee; et al. (Clinical Infectious Diseases, 2021)
Globally, the number of HIV-infected women of child-bearing age conceiving on ART is increasing. Evidence of ART safety at conception and during pregnancy and adverse pregnancy outcomes remains conflicting. The PROMISE 1077 breastfeeding (BF) and formula feeding (FF) international multisite trials provide an opportunity to examine the impact of ART at conception on pregnancy outcomes with subsequent pregnancies. Methods The PROMISE 1077BF/1077FF trials were designed to address key questions in the management of HIV-infected women who did not meet clinical guidelines for ART treatment during the time of the trials. After the period of risk of mother-to-child transmission was over, women were randomized to either continue or discontinue ART. We compared subsequent pregnancy outcomes of non-breastfeeding women randomized to continue ART following delivery, or breastfeeding women randomized to continue ART following breastfeeding cessation who conceived while on ART to women randomized to discontinue ART, who re-started ART after pregnancy was diagnosed. Results Pregnancy outcomes of 939 subsequent pregnancies of 826 mothers were recorded. The intention-to-treat analyses showed increased incidence of low birth weight (<2500gm) for women who conceived while on ART {relative risk 2.65 (95% CI 1.20, 5.81)}, and also a higher risk of spontaneous abortion, stillbirth, or neonatal death {hazard ratio 1.40 (0.99, 1.98)} compared to women who re-started ART after they were found to be pregnant during trial follow up. Downloaded from https://academic.oup.com/cid/advance-article-abstract/doi/10.1093/cid/ciaa805/5860458 by guest on 22 June 2020 Accepted Manuscript Conclusions We found an increased risk for adverse pregnancy outcomes in women conceiving on ART emphasising the need for improved obstetric and neonatal care for this group.
Keywords: Pregnancy outcomes conceiving on ART; Antiretroviral therapy (ART)